Psychological Determinants of Social Dependency in Elderly People During the First Months of Russian-Ukrainian War - Grebin, Nataliia; Hrabovska , Sofiia; Partyko, Tetyana (Journal of Education Culture and Society, 2023)
Aim. The aim of the research is to identify changes of psychological determinants of elderly people’s inclination to social dependency during the first month of Russian-Ukrainian war in comparison with peace time. Methods. The research uses methodologies of inclination to demanding behaviour by Hrabovska (2005), emotional intelligence by D. Luisin (2006), personality volitional qualities by Chumakov (2006), adaptive stress abilities by Rozov (2006), psychological well-being by Ryff as adapted by Shevelenkova and Fesenko (2005). Results. It is identified that during the first months of the full-scale Russian-Ukrainian war, inclination of elderly people, who stay in relatively safe conditions in Ukraine, to social dependency does not undergo significant changes in comparison with peacetime. There are changes in the vector of emotional regulation of social dependency: from intrapersonal in pre-war time into interpersonal during the wartime, when importance in understanding the emotions of other people is high consequently, it results in a more active life stance in the elderly. Initiative becomes a leading will regulator, shows far-sightedness of a person. There is activation of coping mechanisms, related to adaptive thinking, sleep and somatic regulation, and they can be considered vital resources for stable mental health preservation at the beginning of a war. Conclusions. It is recommended to provide psychological support to seniors in finding occupations that help them to realize their capacity for self-sufficiency and create conditions for personal responsibility and assertiveness as the ability to stand for their own rights without violating other people’s resources.